The Principle of Mutability or Flexibility in the Modification of the Contract of Concession of Public Services and Public Works of Infrastructure Subscribed in the Legal Framework of Public-Private Partnerships " - Shimabukuro Tokashiki, Néstor Raúl (2015)
The present article seeks to show the aplication of the mutability principle in amendments on concession contracts that are made on the legal frame of public-private partnership, giving a doctrinaire vision and also the Peruvian normative treatment.